Sport-confidence and learning motivation as joint predictors of basketball skill-learning outcomes in physical education - Fajri Iftitah Rizki; Eval Edmizal; Tjung Hauw Sin; Ronni Yenes (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
Sport-confidence was assessed through the 13-item Trait Sport-Confidence Inventory (TSCI), learning motivation through the 18-item Sport Motivation Scale-II (SMS-II), and basketball skill-learning outcomes through the AAHPERD Basketball Skills Test (speed spot shooting, passing, and control dribble), combined into a composite T-score. Data were studied using Pearson product-moment correlation and multiple correlation with an F-test of significance. Descriptive outcomes showed a high level of confidence (M = 48.69, SD = 8.57) and a high level of motivation (M = 50.93, SD = 6.04) mainly. Sport-confidence was not significantly linked to basketball skill outcomes when taken alone (r =.239, p =.212), and the same for learning motivation (r = -.224, p =.243). However, the two psychological variables taken together predicted a significant portion of variance in skill outcomes (R =.461, R² =.212, F(2, 26) = 3.502, p =.045), which accounted for 21.2% of the variance. These results indicate that confidence and motivation function as complementary rather than independent predictors of motor-skill learning, and that their combined psychological profile, rather than either construct alone, has substantial educational meaning. Since the sample size was quite small (only 29), we consider results from the study as preliminary evidence rather than a thorough test of the hypotheses; however, the fact that 21.2% of the joint variance was explained means that instruction in PE that deals with both confidence and motivation at the same time, rather than treating them as separate targets, could be the one that ultimately results in the greatest practical benefit when it comes to skill acquisition. A discussion of the implications for psychologically informed PE pedagogy and directions for confirmatory research with larger samples is provided.